The Effects of Making Performance Information Public: Evidence from Los Angeles Teachers and a Regression Discontinuity Design - Peter Leopold S. Bergman; Matthew J. Hill (Center for Economic Studies and ifo Institute (CESifo), 2015)
In theory, the publication of performance ratings may improve performance through reputation concerns and peer effects or impede performance by demoralizing employees. This paper uses school-district data and a regression discontinuity design to answer how consumers and employees respond to making performance information public. We find that high-performing students sorted into classrooms with highly-rated teachers as a result of publication. Teachers who were published do not perform better or worse than teachers who were not published on average. This average effect is due to the heterogeneous impact of publication; highly-rated teachers perform worse following publication while low-rated teachers perform better. On net, the gap between high and low-performing students closes slightly as a result.
Keywords: J24; I20; 330